Economic Spillovers, Structural Reforms and Policy Coordination in the Euro Area - Aarle, Bas van.; Weyerstrass, Klaus; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2008)
This book analyses economic interdependence in the Euro Area and provides estimates of the sign and size of economic spillovers and the impact of economic policy coordination concerning structural and budgetary policies on economic performance in the Euro Area. In the different chapters of the book, the following topics are studied: (i) the link between fiscal and monetary policies in the Euro Area; (ii) the link between public debt and long-term interest rates in the Euro Area; (iii) the link between budgetary stabilisation and the level of public debt in the Euro Area; (iv) the spillovers from structural reforms in the Euro Area, (v) the scope for the coordination of fiscal policies and of structural reforms in the Euro Area, and (vi) wage flexibility in the Euro Area.
Economic spillovers, structural reforms and policy coordination in the Euro Area: An overview -- Budgetary spillovers and short-term interest rates -- Budgetary spillovers and long-term interest rates -- Budgetary stabilisation and the level of public debt -- Spillovers from economic reform -- Macroeconomic and welfare effects of structural and budgetary policies: spillovers in the MSG3 model -- Have Europe’s labour markets become more flexible? An exercise in measuring the relative flexibility of wages across countries and time.
Keywords: International economics; European Economic Community literature; Economic policy; Economic growth; Macroeconomics; International Economics; European Integration; Economic Policy; Economic Growth; Macroeconomics/Monetary Economics//Financial Economics